Clay and Organic Amendments on the Nutrient Availability and Enhancing Crop Productivity in Coastal Sandy Soil - Singaravel , R.; Vishwanathan, K.; Dhivya, T. (Research Highlights in Agricultural Sciences Vol. 5, 2022)
Coastal sandy soil lacks texture, structure and shows poor organic carbon, CEC and nutrient retention properties. Among micronutrients, zinc deficiency is occurring in both crops and human. Zinc deficiency is widespread in sandy soil of coastal agro ecosystem owing to low organic matter, CEC, high leaching etc. The role of natural amendments like clay and organics plays a dominant role in improving all these properties. Pot experiments were conducted in the Department of Soil Science and Agricultural Chemistry, Annamalai University to evaluate the influence of clay and organic amendments on the soil properties and yield of rice and black gram in sandy soil. The initial soil sample was characterized as sandy texture with slightly alkaline (pH 8.07) and saline (EC 2.45 dS m-1). The status of N, P and K were low. The following treatments viz., T1–Control (100% recommended NPK), T2–NPK + 20 t clay ha-1, T3–NPK + 40 t clay ha-1, T4 –NPK + 20 t clay ha-1 + FYM @ 12.5 t ha-1, T5 –NPK + 40 t clay ha-1 + FYM @ 12.5 t ha-1, T6 –NPK + 20 t clay ha-1 + Lignite Humic acid @ 20 kg ha-1 and T7–NPK + 40 t clay ha-1 + Lignite Humic acid @ 20 kg ha-1 were studied in CRD using rice ADT-43 with three replications. Another pot experiment was carried out to evaluate the influence of clay and organic amendments viz., FYM and humic acid on the soil properties and Zn availability for black gram in sandy soil. In a Completely Randomized Design, the following treatments namely T1- Control (100% Recommended dose of NPK), T2- NPK + ZnSO4 @ 25 kg ha-1, T3- T2 + clay @ 20 t ha-1, T4- T3 + Humic acid @ 20 kg ha-1, T5- T3 + FYM @ 12.5 t ha-1 were studied using four replications. Black gram variety ADT 3 was grown. In both the crops various growth and yield parameters and yield were recorded. Post harvest soil samples were analysed for the physic-chemical properties, available major nutrients and micronutrient Zn. The results of the pot experiment on rice showed that among the treatments T7, application of N + clay @ 40 t ha-1 + HA @ 20 kg ha-1 recorded highest soil available nutrients viz., NH4+-N (48.26 mg kg-1), NO3- -N (36.33 mg kg-1), Olsen P (5.13 mg kg-1) and NH4OAc-K (91.21 mg kg-1) at harvest stage respectively. This treatment also recorded the highest yield character and yield of rice. The results of the study on black gram indicated that the application of both the amendments were efficient in improving the growth, yield of black gram and also Zn availability and Zinc use efficiency. Among the treatments T4, application of NPK + ZnSO4 @ 25 kg ha-1 + clay @ 20 t ha-1+ Humic acid @ 20 kg ha-1 accounted for a significant increase in the DTPA-Zn content in soil besides improving the organic carbon and available nutrient status.